Organizational Change Dynamics and Their Impact on Employee Well-Being: A Quantitative Exploration within a Moroccan Hotel Chain - TAOUSSI, Ghita; AFILAL, Khaoula (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to examine the effect of organizational change on the health and well-being of employees, a topical issue in the contemporary professional environment. The study focuses on a case of a Moroccan hotel company, providing an original insight into the hotel industry in Morocco. The main goal is to explore the links between the dimensions of organizational change and the health and well-being of employees, in order to determine how organizations can optimize the management of these transformations. The research adopts a quantitative approach, including the collection of primary data from the employees of the hotel chain, followed by the validation of the instruments and a rigorous statistical analysis. The results show that the clarity of the goals and the vision of the change is essential for the health and well-being of employees. Moreover, the involvement of employees in the decisions related to the change has a positive influence on their health and well-being. However, the role of communication in the change process has not been verified significantly. These findings have practical implications for managers, highlighting the importance of clarity in communicating the goals and the involvement of employees in the decision-making process. They suggest strategies to improve the health and well-being of employees and their adaptation to the change, fostering a more positive and productive work climate.